The Effectiveness of the Discovery Learning Model Assisted by the Mathematics Learning Module on Mathematical Problem-Solving Skills - Muhammad Habib Ramadhani; Kartono; Sri Haryani (Jurnal Pendidikan Indonesia, 2023)
This research is motivated by the low skills of students in solving mathematical problems, where problem solving skills are one of the important skills of the 21st century. This research aims to analyze the effectiveness of the discovery learning model assisted by the mathematics learning module on students' mathematical problem-solving skills. This type of research is quasi-experimental. The research design used is Non-equivalent Control Group Design. The research was conducted in the fifth grade in two elementary schools. The instrument used in this research was a test instrument consisting of 8 essay questions. Data analysis techniques using parametric statistical tests. The research results obtained: 1) the average mathematical problem-solving skills of students in the experimental group reached the passing grade; 2) the proportion of experimental class students who achieved a passing grade was more than 75%; 3) the average experimental mathematical problem-solving skills is higher than the control group; 4) students' mathematical problem-solving skills in the experimental group have increased (n-gain) with the criteria of "high." Based on the results of the research, it can be concluded that learning using the discovery learning model assisted by the mathematics learning module is effective in improving students' mathematical problem-solving skill.